Assessing Sharia Monetary Instruments Against Country Economic Growth - Wahid, Arfian Nur; Jamel, Surono bin; Noviarita, Heni; Anggraini, Erike (JEJAK: Jurnal Ekonomi dan Kebijakan, 2020)
This study aims to examine the effect of Islamic monetary instruments on Indonesia's economic growth. Statutory Reserves, Bank Indonesia Syariah Certificate (SBIS) and Outstanding Deposit Facility Syariah (FASBIS) are used as sharia monetr instrument variables in observations. this study is a quantitative study using monthly time series data obtained from the publication of Bank Indonesia and the Indonesian statistical agency in 2015-2019 using ARDL analysis. The results of this study indicate that both short-term and long-term modeling, instrument variables Islamic monetary does not have a significant relationship on economic growth. Although it has a very small effect, the Demand Deposits variable has an effect on the Indonesian economy, while the other variables observed have an inverse relationship with the variable of Indonesia's economic growth. the achievement of monetary stability through sharia monetary instruments can be optimized using policies on the minimum statutory reserves in banks that are useful for controlling the circulation of the amount of money in society so that it is more stable and the Indonesian economy can grow through the middle income trap.